DIGITAL PRESERVATION DI ERA INFORMASI: SEBUAH TANTANGAN PERPUSTAKAAN SEBAGAI AGENT OF CHANGE - Cahyaningtyas, Dwi Fitrina (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 5 No 1 (2025), 2025)
In a library, there are so many progam  which is offered to give the best services for users. One of the progam that library offered is digital preservation in information era .   D igital preservation are already being developed in librar y . The library as an institution doing a lot of activities in collecting, processing, preservation, and Dissemination of Knowledge and Culture, in this era, digital preservation should be develop e to facilitate user . Moreover, the collection of library mostly has integrated in a digital . The activities of preserving digital material into something inevitable or become a necessity.   I t concerns the existence and continuity of the values of information held by the library. An information becomes valuable when easily searchable and found. Preservation of digital material is intended that the information stored in digital format easily accessible and available in the long term (accessible and yet well preserved). In this article, the writer will explain the difference s of digitization and digital preservation, and to get a overview of the current state of digital preservation.